2013
DOI: 10.1021/mz300660t
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2-deoxy-2-methacrylamido glucopyranose)-b-Poly(methacrylate amine)s: Optimization of Diblock Glycopolycations for Nucleic Acid Delivery

Abstract: A series of nine poly(2-deoxy-2-methacrylamido glucopyranose)-b-poly(methacrylate amine) diblock copolycations The cationic block was varied in length and in the degree of methyl group substitution (secondary, tertiary, quaternary) on the pendant amine in an effort to optimize the structure and activity for plasmid DNA delivery. Upon a thorough kinetic study of polymerization for each polymer, the glycopolymers were prepared with well-controlled Mn and Ð. The binding and colloidal stability of the polymer-pDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 28 publications
4
73
0
Order By: Relevance
“…9,10 The polyplexes formed from this series of diblock glycopolymers exhibited colloidal stability in cell media and had relatively low cytotoxicity. Moreover, both amine type and cationic charge block length were demonstrated to greatly affect transgene expression efficiency in vitro.…”
Section: Resultsmentioning
confidence: 98%
“…9,10 The polyplexes formed from this series of diblock glycopolymers exhibited colloidal stability in cell media and had relatively low cytotoxicity. Moreover, both amine type and cationic charge block length were demonstrated to greatly affect transgene expression efficiency in vitro.…”
Section: Resultsmentioning
confidence: 98%
“…Also, it should be noted that both pMAT- b -AEMA-2 and- 3 polyplex formulations at N/P = 7 had cell uptake comparable to that of PEG- b -AEMA. 23,44 …”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that differences between some samples are not statistically significant, but the general trend that appears in the uptake assays as well as gene expression studies for both cells lines correlates with previous work in the field. 23,41,44,46 …”
Section: Resultsmentioning
confidence: 99%
“…The diblock glycopolymers however, gave a low zeta potential value when it was dissolved in acetate buffer as polymer solutions were prepared at 1 mg mL −1 of polymer of acetate buffer solution, therefore resulting in less cationic groups in the same volume of solutions. It has also been reported that excessive positive charges can lead to cytotoxicity and therefore the carbohydrate groups here can assist by lowing the toxicity and preventing colloidal aggregation in cell culture media …”
Section: Resultsmentioning
confidence: 94%
“…Trehalose which comprise of two linked (1→1) α ‐glucose units increased the stability of formed polyplexes for lyophilization and the delivery of pDNA in vivo . In the same research group, poly(2‐deoxy‐2‐methacrylamido glucopyranose)‐ b ‐poly(methacrylate amine) were synthesized and found that the glucose based cationic glycopolymers resulted in very effective pDNA delivery and polymers displayed low cytotoxicity profiles . However, there are only a few articles reporting the synthesis of mannose based cationic glycopolymers .…”
Section: Introductionmentioning
confidence: 99%